ANALISIS MODEL INTERVENSI LOGOTHERAPI DALAM MENGATASI MASALAH PSIKOLOGIS PESERTA DIDIK - Abdul Hasib (Bajang Institute, 2024)
This research aims to analyze logotherapy as one of the intervention models in reducing the psychological burden experienced by students. Psychological burden on students can include academic stress, anxiety, depression, and other emotional issues that can hinder their development and well-being. The research method involves a literature review of relevant studies on the use of logotherapy in an educational context. The analyzed data include the effectiveness of logotherapy in reducing psychological burden, improving quality of life, attitude changes, and enhancing students' motivation to learn. The research also involves qualitative analysis of the experiences and perspectives of students who have undergone logotherapy interventions. The results of the analysis indicate that logotherapy can be an effective approach in reducing psychological burden in students. In an educational context, logotherapy helps students to find meaning and purpose in their lives, develop a sense of responsibility, and face challenges with a positive attitude. Logotherapy can also enhance life satisfaction, improve interpersonal relationships, and encourage higher levels of learning motivation. These findings have important implications in the field of education. By implementing logotherapy as a psychological intervention, educational institutions can help students overcome the psychological burdens they experience and improve their mental well-being